Public policy : why ethics matters - Boston, Jonathan, 1957-; Bradstock, Andrew; Eng, David L., 1967- (ANZSOG (Series), 2010)
"Ethics is a vigorously contested field. There are many competing moral frameworks, and different views about how normative considerations should inform the art and craft of governmental policy making. What is not in dispute, however, is that ethics matters"--